Folksonomy: the language of the tags - Assis, Juliana de; Moura, Maria Aparecida (Encontros Bibli: revista eletrônica de biblioteconomia e ciência da informação, 2013)
The radicalization of the collaborative potential of the current web shows a trend of customization of information retrieval through tools that exploit the natural language in representation of content across social networks and its sharing. Such socio-technical configuration brings challenges to information professionals for both the description and understanding of informational phenomena that occur in this area, and for the preparation of products and services for a user who is consolidating herself as an informational subject by assuming an active role vis-a-vis the complexity that characterizes the organization of information in digital contexts. This paper presents research findings related to the analysis of language used in three collaborative environments that use the folksonomy (social tagging systems). From a perspective grounded in Semiotics and Social Network Analysis, it is identified and described the main manifestations of the language generated by social networks and shared across the environments that exploit folksonomies.